Qualitative Exploration of Barriers to Medication Adherence Among Patients with Uncontrolled Diabetes in Saudi Arabia - Ghaida Alodhaib; Imtinan Alhusaynan; Ahmer Mirza; Yasser Almogbel (MDPI AG, 2021)
Uncontrolled diabetes is associated with macrovascular and microvascular complications that compromise the quality of life; however, the patients' perspectives about medication non-adherence are unclear. We aimed to understand patient behavior and explore the barriers to medication adherence in uncontrolled diabetes patients. We employed a qualitative method of face-to-face interviews conducted with adult patients in Saudi Arabia who had uncontrolled diabetes mellitus (glycosylated hemoglobin >7% or fasting blood glucose >7.2 mmol/L). All interviews were audio-recorded and analyzed using thematic analysis. The interviews were conducted for 68 patients. Sixty-seven patients were suffering from Diabetes Mellitus Type 2, and one patient was suffering from Diabetes Mellitus Type 1. We identified the barriers to medication adherence and classified them under six main factors: patients-, medications-, healthcare-, provider-, social-, and disease-related factors. The main barriers identified were the use of alternatives, hard-pressed for time, polypharmacy, bad relationship with the physician, cultured beliefs, self-alteration of the dose, exposed side effects, ineffective medications, refusal of insulin, multiple doctor visits, uncontrolled diet, and forgetfulness. Multiple barriers that prevented the patients from medication adherence were related to poor knowledge, counseling, psychological management, and social support. Appropriate educational programs, suitable patient-specific counseling, and close follow-ups would be required to improve the knowledge, outcomes, and quality of life in uncontrolled diabetes patients.